(untitled) (Health Renaissance, 2011)
Background: Short-term or long-term physical exercise is associated with reductions in anxiety. Cerebral lateralization hypothesis predicts that anxiety reductions caused by exercise is due to decrease in right, relative to left, hemisphere activation. However, research reports on difference in anxiety reduction in response to short-term exercise are scanty. Objective: This study was aimed to compare the effect of acute bout of aerobic exercise on electroencephalographic (EEG) frontal alpha activity and anxiety between genders, and correlate between them. Method: A cross-sectional study was conducted on healthy 30 adult (male=15, female=15) subjects. They bicycled on automated ergometer, maintaining 50% HRmax for 20 min. EEG was recorded from frontal and occipital region (Fp, F1, F2, O1, and O2) and anxiety-scores were recorded before and after exercise. Results: Frontal EEG alpha activity power was significantly greater in females (p<0.001) than in males both in left (females=106.87±34.20 vs. males=53.68±7.90 µV2) and right hemispheres (females=127.62±36.45 vs. males=48.33±8.18 µV2) pre-exercise; and also in left (females=97.97±40.74 vs. males=54.12±10.73 µV2) and right (females=116.01±54.70 vs. males =58.53±15.43 µV2) hemispheres post-exercise. However, only males showed a statistically significant increase in right frontal activity (right=48.33±8.18 to 58.53±15.43 µV2, p<0.01) post-exercise. Only males showed a significant negative correlation between pre-exercise state-anxiety and right frontal alpha activity (r value= -0.634, p<0.05). Conclusions: Our study suggests that females have positive affect at rest than males. In both genders, exercise reduced anxiety scores. However, only males supported cerebral lateralization hypothesis and negative association between resting frontal asymmetry and state-anxiety. Keywords: acute aerobic exercise; anxiety; frontal alpha asymmetry; gender DOI: 10.3126/hren.v8i3.4207 Health Renaissance, September-December 2010; Vol 8 (No.3);152-157